2006
DOI: 10.1103/physrevlett.96.125004
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Wake Emission of High-Order Harmonics from Overdense Plasmas

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
234
0
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(253 citation statements)
references
References 16 publications
14
234
0
5
Order By: Relevance
“…2) suggest that the CWE mechanism provides a dominant contribution in our experiments. In fact, CWE was found to show a well-defined cut-off that moves to higher energy for increasing density 15,18 (see Supplementary Information) as can be seen by comparing the spectra in Fig. 2a,c with those in Fig.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…2) suggest that the CWE mechanism provides a dominant contribution in our experiments. In fact, CWE was found to show a well-defined cut-off that moves to higher energy for increasing density 15,18 (see Supplementary Information) as can be seen by comparing the spectra in Fig. 2a,c with those in Fig.…”
mentioning
confidence: 67%
“…One is based on a relativistic Doppler upshift of the laser light reflected off the oscillating plasma surface, acting as a relativistic oscillating mirror (ROM; refs 6,7). The other originates from currents excited by fast electrons in the density ramp of the plasma-vacuum interface leading to what has been dubbed coherent wake emission (CWE; refs 15,17). CWE is dominant at sub-or moderately relativistic intensities 17,18 for a L < 1, whereas ROM becomes more efficient for a L > 1 and completely takes over in the highly relativistic regime 12,19 , when a L 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The harmonic emission emanating from the interaction of intense laser pulses with solid-density plasma is due to two main mechanisms. For relatively low laser intensities, the so-called coherent wake emission mechanism (CWE) dominates [11,12]. Under these circumstances, it has been recently demonstrated that the harmonic emission leads to temporal bunching with attosecond pulse durations [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This can be seen as the time-reverse of resonant absorption [22], where laser light is partially converted into collective electron oscillations in a gradient of plasma density (both effects correspond to linear mode conversion mechanisms [22,23]). This emission, known as coherent wake emission or CWE [24], consists of a sub-femtosecond burst of coherent radiation, superimposed with the laser light reflected at the plasma surface [25], with a spectrum extending into the extreme ultraviolet (XUV) up to ωmax = N solid /Nc ωL, emitted from the region of solid plasma density N solid (Fig. 1b).…”
mentioning
confidence: 99%